Good morning my avocado tree - International Livestock Research Institute (International Livestock Research Institute, 2019)
The Africa RISING project in Ethiopia is enhancing smallholder farming by encouraging farmers to intercrop trees and food crops. In the Lemo Woreda, this approach has boosted avocado production helping farmers diversify their diets and increase their incomes.